2023
DOI: 10.1101/2023.11.22.568209
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-related differences in electrophysiological correlates of visuospatial reorientation

Clément Naveilhan,
Alexandre Delaux,
Marion Durteste
et al.

Abstract: Spatial navigation abilities decline with age. Recent studies revealed a specific impairment in landmark-based reorientation, linked to changes in scene-selective brain regions activity. While fMRI studies suggest that these cortical modulations might be compensatory, a more precise investigation of the brain dynamics associated with visuospatial processing is warranted. We analyzed Event-Related Potentials and Event-Related Spectral Perturbations recorded from electrodes over scene-selective regions. 28 young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
(154 reference statements)
0
1
0
Order By: Relevance
“…This sample size was determined by a priori power analysis using G*Power (version 3.1.9.7; Faul et al, 2007). The power analysis was based on data from a previous ERP study investigating behavioral and neural differences between young and older adults during a landmark-based reorientation task contrasted with a passive scene perception (Naveilhan et al, 2023). Analysis of the young participants’ data indicated that a minimum of 23 participants was required to achieve a power of 0.95 at an alpha level of 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…This sample size was determined by a priori power analysis using G*Power (version 3.1.9.7; Faul et al, 2007). The power analysis was based on data from a previous ERP study investigating behavioral and neural differences between young and older adults during a landmark-based reorientation task contrasted with a passive scene perception (Naveilhan et al, 2023). Analysis of the young participants’ data indicated that a minimum of 23 participants was required to achieve a power of 0.95 at an alpha level of 0.05.…”
Section: Methodsmentioning
confidence: 99%